INCREASING THE EFFICIENCY OF ARTERIAL HYPERTENSION DISPENSARY CARE IN A FAMILY CLINIC - Shakhzada S. Gulyamova (Western European Studies, 2025)
Effective control and active clinical observation of patients with arterial hypertension (AH) implies both the correctness of medical prescriptions (selection of medicine, dose, medication regimens, etc.), and regular correction of main risk factors for cardiovascular diseases (CVD), closely related to lifestyle. In this article, we describe the survey on the awareness of patients with arterial hypertension and the implementation of the “Algorithm of computer program for personalized dynamic management of patients with arterial hypertension in primary health care”. This computer program (software) will enable toidentify the risk of progression of disease complications at their early stage of development and to carry out proper treatment. The past 5-year data from 222-randomly selected outpatient cards of hypertensive patients, who were followed up at a family polyclinic (n=54) and in a number of rural health clinics (n=168) of the Republic of Uzbekistan, were retrospectively analyzed. The findings of the analysis were compared with the results of patient study (questioning, examination, anthropometry, blood pressure measurement, determination of cholesterol, etc.). The physicians from the Tashkent family polyclinic and rural health clinics of a number of the Republic’s regions, who had taken 10-month retraining courses for general practitioners, were questioned. Questionnaires were used to study 156 and 119 physicians before and after retraining, respectively.
Keywords: arterial hypertension; risk factors; awareness of hypertensive patients